The study of informational content of special physical and technical parameters of preparedness of qualified athletes - Кутек Тамара Борисівна (Tamara Kutek) (Slobozhanskyi Herald of Science and Sport, 2015)
This author is analyzing the informational content, which characterize the special physical and technical preparedness of qualified high-jumpers with a running start. Purpose: to study the most informative parameters of special physical and technical preparedness of qualified high-jumpers with a running start and to determine their correlation with the sports result. Material and Methods: analysis and generalization of scientific literature, pedagogical observation (interview, survey), factor analysis and correlation analysis. 27 leading trainers of Ukraine took part in the research. Results: it has been estimated that 35% of trainers consider inexpedient to use current parameters on special physical and technical preparedness of high-jumpers with a running start due to the low level of informational content of the obtained data and doubtful correlation with the sports result. Conclusions: The selected the tests of special physical and technical preparedness, which are necessary to further develop the methodology of forecasting the effectiveness of high-jumpers.